PROSES PEWARISAN PADA MASYARAKAT HUKUM ADAT SAIBATIN (PESISIR) DI KABUPATEN TANGGAMUS PROVINSI LAMPUNG - , Nawawi ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study aimed to know and understand (1) a variety of property became an object of inheritance among the indigenous people of Lampung Coastal Saibatin or (2) The heirs of the estate division (3) The pattern of distribution of inheritance among the indigenous people of Lampung Saibatin or Coastal (4) Role of PPAT in the process of division of inheritance among the indigenous peoples of Lampung Saibatin or Coastal. This research was conducted by a normative approach and empirical approach. Normative approach includes a study of the principles, terms and provisions of law, both written and unwritten. Empirical approach is to obtain facts about the behavior of law-related subject matter. The nature of this research is descriptive analytic. This study was conducted in Tanggamus District includes the Sub district Kota Agung, Sub district Talang Padang and Sub district Cukuh Balak. The subject of the research done by purposive sampling consisted of 30 respondents who had received and shared heritage, 7 (seven) traditional leaders and 3 resource persons PPAT. The primary data obtained through interview and questionnaire techniques, while the secondary data obtained through the research literature and analyzed qualitatively.. The results showed that the basic property that the object of inheritance among the indigenous peoples of Lampung Coastal (Saibatin) still follow norm of local customary law. Heirs within Lampung Coastal indigenous people (Saibatin), also still follow the traditional rules, there are only changes to the existence of a widow or widower as an heir. In addition, in the local community are also known other heirs of those who formerly close to the deceased and the person appointed by the relationship of brotherhood (mewarei). The pattern of inheritance among the indigenous peoples of Lampung Coastal (Saibatin), implemented through two stages: first, before the heir's death, which in this case the estate is distributed directly to the beneficiary and grants, which will grant executed after heir dies . Second, after heir dies, inheritance is done through two negotiations. First held a family meeting to determine the respective heirs and relatives of The second deliberation to carry out the distribution of the estate which in this case witnessed by the local traditional leaders and village heads. Officer Role Manufacturer Deed Land (PPAT) / PPAT Camat in the process of inheritance. In this case PPAT deed transfer role in making the land rights that is in the making of deed transfer that can be used as authentic evidence to holders of land rights. To transfer rights to the land because of inheritance, especially for the indigenous poeple in the transition using Camat as PPAT (ex officio).